The Effect of Fever Medicine Advertising on Television onPurchase Decisions Fever Medicine in RW 01 Cipedak Jagakarsa South of Jakarta - Wulandari, Ainun; Fiandani, Afifah (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2023)
Advertising is a form of non-personal communication activity delivered through the media by paying for the space it uses to convey messages that are persuasive, reminding, and offering a product to consumers by companies, non- commercial institutions, and interested individuals. Advertising can affect the feelings of someone who sees it, so that it can influence purchasing decisions. The purpose of this study was to determine the effect of fever medicine advertisements on television on purchasing decisions for fever medicine in the community of RW 01 Cipedak, Jagakarsa, South of Jakarta. This research was an observational study with a quantitative descriptive cross sectional method. The number of respondents obtained was 120 people. The sampling technique in this study used cluster random sampling. Data obtained through questionnaire. The research results obtained that the advertising variable has a positive effect on people's attitudes with sig. 0.000 (p value <0.05), the public attitudes variabel has a positive affect on purchasing decisions with sig. 0.000 (p value <0.05). The results showed that advertisements for fever medicine on television indirectly influenced the purchasing decisions of fever medicine for the people of RW 01 Cipedak Village, Jagakarsa Distrik, South Jakarta.